Answer:
![-1\frac{1}{2}](https://tex.z-dn.net/?f=-1%5Cfrac%7B1%7D%7B2%7D)
Step-by-step explanation:
We have two coordinate points and are asked to find a slope.
When finding slope, we can use the formula listed :
![\frac{y^2-y^1}{x^2-x^1}}](https://tex.z-dn.net/?f=%5Cfrac%7By%5E2-y%5E1%7D%7Bx%5E2-x%5E1%7D%7D)
To understand what the variables are, you can take this :
![(x^1,y^1)](https://tex.z-dn.net/?f=%28x%5E1%2Cy%5E1%29)
![(x^2,y^2)](https://tex.z-dn.net/?f=%28x%5E2%2Cy%5E2%29)
Substitute the points :
![(-1,4)](https://tex.z-dn.net/?f=%28-1%2C4%29)
![(5,-5)](https://tex.z-dn.net/?f=%285%2C-5%29)
Now substitute it into the formula :
![\frac{-5-4}{5-(-1)}](https://tex.z-dn.net/?f=%5Cfrac%7B-5-4%7D%7B5-%28-1%29%7D)
![\frac{-3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-3%7D%7B2%7D)
![-1\frac{1}{2}](https://tex.z-dn.net/?f=-1%5Cfrac%7B1%7D%7B2%7D)
Step-by-step explanation:
Let's represent the two integers with the variables
and
.
From the problem statement, we can create the following two equations:
![x + y = -7](https://tex.z-dn.net/?f=x%20%2B%20y%20%3D%20-7)
![xy = 12](https://tex.z-dn.net/?f=xy%20%3D%2012)
With the first equation, we can subtract
from both sides to isolate the
variable to the left-hand side:
![x = -7 - y](https://tex.z-dn.net/?f=x%20%3D%20-7%20-%20y)
Now that we have a value for
, we can plug it into the second equation and solve for
:
![(-7 - y)y = 12](https://tex.z-dn.net/?f=%28-7%20-%20y%29y%20%3D%2012)
![-7y - y^{2} = 12](https://tex.z-dn.net/?f=-7y%20-%20y%5E%7B2%7D%20%3D%2012)
Now, let's move everything to one side of the equation:
![y^{2} + 7y + 12 = 0](https://tex.z-dn.net/?f=y%5E%7B2%7D%20%2B%207y%20%2B%2012%20%3D%200)
Factoring this quadratic will give us two values for
:
![(y + 4)(y + 3) = 0](https://tex.z-dn.net/?f=%28y%20%2B%204%29%28y%20%2B%203%29%20%3D%200)
![y = -3, -4](https://tex.z-dn.net/?f=y%20%3D%20-3%2C%20-4)
Since we now know
, we can plug this back into either of the original equations to get a value for
, which will be
.
So the two numbers that sum to
and have a product of
are
.
Answer:
Both expressions are = to 11 when x is 2.
Therefore, the expressions are equivalent.
Answer:
Step-by-step explanation:
1/4 x 2 = 2/4
2/4 simplified = 1/2
Answer:
2 and 8, 3 and 5
Step-by-step explanation:
uh no explanation needed